(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper Model Predictive Control (MPC)for SISO LTI system is considered. MPC emanates from dynamicoptimisation where a dynamical system is controlled while minimising the associated performance index and satisfying all the constraints.Using current measurement of states (if all states are available for measurement elsestate observer is used) a predicted plant model is obtained on a prediction horizon (N) and using this predicted plant model we get the predicted performance index which is minimized to get a future control sequence. The first component of the control sequence is used while rest gets discarded and the at the next instance the whole process is repeated. In this paper a LTI SISO system is subjected to constraints on both input and output is considered. Simulation results verify the efficacy of the designed algorithm.